2016
DOI: 10.1080/10942912.2016.1223127
|View full text |Cite
|
Sign up to set email alerts
|

Aging kinetics of low amylose rice during storage at ambient and chilled temperatures

Abstract: The objectives of this study were to monitor the changes in rice properties during aging and to compare kinetic parameters related to some of those changes. Paddy of three low amylose rice varieties was stored at ambient (30 ± 2ºC) and chilled (8 ± 2ºC) temperatures for 9 and 18 months, respectively. Aging led to a decrease in solid loss, peak viscosity, breakdown, and adhesiveness and an increase in head rice yield, minimum cooking time, water uptake, volume expansion, pasting temperature, final viscosity, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Hayashi and Yanase () also found that red rice often changed to a darker reddish‐brown hue during postharvest storage, as a result of changes occurring in pre‐existing chemical species, especially the decreasing polyphenol contents and oxidative degradation of proanthocyanidin pigments. Jungtheerapanich, Tananuwong, and Anuntagool () demonstrated a decrease in whiteness of rice stored at ambient temperature (30 °C) for 9 months. Park, Kim, Park, and Kim () found that the greater the storage temperature (30 and 40 °C), the lower the whiteness of normal rice during storage.…”
Section: Effects Of Storage On Rice Grain Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Hayashi and Yanase () also found that red rice often changed to a darker reddish‐brown hue during postharvest storage, as a result of changes occurring in pre‐existing chemical species, especially the decreasing polyphenol contents and oxidative degradation of proanthocyanidin pigments. Jungtheerapanich, Tananuwong, and Anuntagool () demonstrated a decrease in whiteness of rice stored at ambient temperature (30 °C) for 9 months. Park, Kim, Park, and Kim () found that the greater the storage temperature (30 and 40 °C), the lower the whiteness of normal rice during storage.…”
Section: Effects Of Storage On Rice Grain Qualitymentioning
confidence: 99%
“…Although the extent of increase (about 2%) in HRY was smaller than laboratory storage cases (approximately 10%), the influence of rice storage duration on HRY was significant (Ranalli et al., ). The increase of HRY may be due to more agglomeration of starch granules (Soponronnarit et al., ), thus enhancing the endurance of the rice kernels during milling (Jungtheerapanich et al., ). However, Manski, Matsler, and Siebenmorgen () did not find significant differences in HRY of stored medium and long rice grains at any storage temperatures after harvest.…”
Section: Effects Of Storage On Rice Grain Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Protein forms a strong network around starch, which limited the expansion and softness of starch. Therefore, after cooking, the hardness of aged rice increased and its viscosity decreased (Jungtheerapanich et al, 2017;Dutta et al, 2012). Studies have shown that the total protein content of rice grain was basically unchanged during aging, but its extraction rate had decreased.…”
Section: Effects Of Rice Aging On Physicochemical Properties Of Storamentioning
confidence: 99%
“…Rice being the primary staple food of more than half of the world's population requires adequate storage with preservation of its eating quality to ensure uninterrupted supply to end users all year round(Thongrattana 2012). Storage of rough and milled rice undergoes a wide range of physicochemical changes on the characteristics of rice such as pasting properties(Ziegler et al 2017), thermal properties(Faruq et al 2015;Ziegler et al 2017), and textural changes in the cooked rice over a time period(Nawaz et al 2017;Zhou et al 2007b;Keawpeng & Venkatachalam 2015;Jungtheerapanich et al 2017).…”
mentioning
confidence: 99%